Ethnography from the mission field : the Hoffmann Collection of Cultural Knowledge - Hoffmann, C. 1868-1962. (Religious Studies, Theology and Philosophy E-Books Online, Collection 2015, ISBN: 9789004287471., 2015)
In Ethnography from the Mission Field: The Hoffmann Collection of Cultural Knowledge Joubert and others offer a translated and annotated edition of the 24 ethnographic articles by missionary Carl Hoffmann and his local interlocutors published between the years 1913 and 1958. The edition is introduced by a historic contextualisation using a cultural historical approach to analyse the contexts in which Hoffmann's ethnographic texts were produced. Making use of historical material and Hoffmann's own words from personal diaries and letters, the authors convincingly draw the attention to the discursive context in which the texts annotated in this book had been compiled. In a concluding chapter the book traces the captivating developments of the orthography of Northern Sotho through Hoffmann's texts over almost half a century. Brill has made the documentary film "A Journey into the Life of a Mission-Ethnographer" which is interlinked with this book available online via its online channels. To access it please click here . The digital database of the "Hoffmann Collection of Cultural Knowledge" (HC-CK) can be accessed by clicking here . It is an amalgamation of digital scans, images and video footage relating to missionary Carl Hoffmann's work and life on various mission stations, made available by the Humboldt Universität zu Berlin.